Geoinformação aplicada a saúde pública: avaliação dos casos de violência contra a mulher no município de Santa Maria, RS - Souza, Martha Helena Teixeira de (2008)
The development implemented of technologies through mathematical models and computational advances, has allowed establish and study the interfaces that permeate the relations of the geographical area in the health area. These considerations can be extended to cases of violence against women, seen since 1993 as a problem of public health by the United Nations having serious effects on their health. The health services have a difficult operating activities in the planning, implementation and impact assessments for the actions of prevention and therefore occurs in large part, by lack of adequate spatialization of factors that characterize the populations with greater vulnerability to diseases and disorders occurring more frequently in public health. This work aimed at general identify and map the areas of greatest vulnerability for cases of against women violence reported through Region Police Office Women's through the modeling of variables in a of geographic information system with a view to violence linking and its factors associated. How specific objectives: identify, tag and register all variables that can contribute in the mathematical modeling that allows characterize the areas of vulnerability of the occurrence against women violence, modeling and implement a spatial database with the introduction of data from bodies responsible for public health data collected in the field, data analysis of the consistency and generated information, which can be arranged in spatial design and plans of information. Develop a mathematical model that enables understanding of correlations between variables / factors that characterize the vulnerable population against women to violence. This is a quantitative study of the diseases distribution, where the object of study is called spatial analysis in health and has as one of its applications to exploratory analysis of violence data reported. As results obtained that 64.7% of women surveyed have up to 38 years of age, 84.6% of the notifications of the victims of violence have schooling and average being 57.3% of the cases the violence has been practised by the partner or ex companion.